Pelvic floor muscle training and postural balance in elderly women: An exploratory single arm trial - Loyolla Montanari Leme, Gianluca [UNESP]; Baldini Prudencio, Caroline [UNESP]; Thomaz de Aquino Nava, Guilherme [UNESP]; Mércia Pascon Barbosa, Angélica [UNESP]; Scheicher, Marcos Eduardo [UNESP] (Elsevier, 2022)
Introduction: To investigate the influence of a training of mobility, gait speed and postural balance of pelvic floor muscles (PFM). Methods: A single-arm clinical trial study was approved and registered at the Brazilian Clinical Trials Registry (RBR-4rxhd4). Eighteen women over the age of 60 with pelvic floor dysfunction complaints were subjected to 10 sessions of functional electrical stimulation and digital palpation of PFM. Mobility and gait speed were evaluated by the Timed up and Go and the 10-m walk tests respectively. Standing balance was evaluated using a force plate. Results: No significant differences were found in mobility, gait speed, and standing balance. PFM contraction worsened mobility, gait speed, and standing balance performance. Conclusions: The training protocol enhanced PFM strength and endurance, but the improved ability to recruit PFM did not positively affect balance, mobility, and gait speed.
Keywords: Aging; Pelvic floor; Postural balance; Rehabilitation